Grain size effects in the deformation of [0 0 0 1] textured nanocrystalline Zr - Ruestes, C. J. (2013)
Molecular dynamics was used to simulate tensile testing of columnar grain samples of nanocrystalline Zr with random rotations around the [0 0 0 1] axis. For grain sizes smaller than a critical size the results show an inverse Hall–Petch effect. For larger grains the calculated Hall–Petch constant agrees well with the experimental data. Grain size effects on deformation mechanisms, including grain boundary sliding and dislocation emission, are also discussed.